5 - Réflexion sur la Fonction Objectifs de L'entreprise: by Amadou Lamine DIA - Amadou Lamine DIA, (Africa Development, 1988)
Business enterprises have various objectives. As a rule these are of two types: economic and social. Economic objectives cover profit - making, growth, business flexibility and autonomy. Contrary to these, the achievement of social objectives requires that a num ber of other needs are met: salary increase, better working conditions and necessitates exte nal inputs from public authorities, banks, consumers. However a firm - and especially African firms - can only survive when a consensus is reached on the basis of an adequate proportion of economic profits and adequate social gains. In fact the equilibrium of com panies depends on whether they are sufficiently efficient at the economic level to both main tain their competitive capacity and to satisfy the personal claims of the different partners. I this regard, it is easier for medium-size businesses to make profits from consensus-based o jectives than bigger enterprises which instead make more competitive profits from central ized strategies that are directly applied to production units. Yet a consensus never has a final character. Off and on it is challenged by any of the partners who strives to maximize the gains in accordance with the prevailing balance of forces. The survival of the firm results from the opposition and negotiation processes as they lead to a compromise. However, such a compromise is constantly challenged; it is not static.